2014
DOI: 10.1002/2013wr014531
|View full text |Cite
|
Sign up to set email alerts
|

Embedded resource accounting for coupled natural‐human systems: An application to water resource impacts of the western U.S. electrical energy trade

Abstract: In complex coupled natural-human systems (CNH), multitype networks link social, environmental, and economic systems with flows of matter, energy, information, and value. Embedded Resource Accounting (ERA) is a systems analysis framework that includes the indirect connections of a multitype CNH network. ERA is conditioned on perceived system boundaries, which may vary according to the accountant's point of view. Both direct and indirect impacts are implicit whenever two subnetworks interact in such a system; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 89 publications
(91 reference statements)
1
57
0
Order By: Relevance
“…Using the commodity (2.2) and labor (2.3) approaches to calculating virtual water flows, a net water footprint was calculated for each PMA municipality and for the metropolitan area using the Embedded Resources Accounting (ERA) framework [16,17]. Used in this context, ERA is a minor variation on the standard Water Footprint Assessment (WFA) [75] notation that accounts for a hierarchy of nested boundary conditions by disaggregating the internal water footprint term to reveal internal virtual water flows between entities inside a boundary.…”
Section: Disaggregation By Scale and Boundary Of A Municipality's Watmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the commodity (2.2) and labor (2.3) approaches to calculating virtual water flows, a net water footprint was calculated for each PMA municipality and for the metropolitan area using the Embedded Resources Accounting (ERA) framework [16,17]. Used in this context, ERA is a minor variation on the standard Water Footprint Assessment (WFA) [75] notation that accounts for a hierarchy of nested boundary conditions by disaggregating the internal water footprint term to reveal internal virtual water flows between entities inside a boundary.…”
Section: Disaggregation By Scale and Boundary Of A Municipality's Watmentioning
confidence: 99%
“…Indirect or virtual water dependencies are concentrated within the same local hydrology and physical water supply upon which the PMA directly depends for its water supply, rather than being spatially distributed to hydrologically diversified regions. This large circular virtual water trade within the PMA and large dependency within the Southwestern US region and Colorado River Basin amplifies the community's hydro-economic exposure to scarcity and disruption of the local water resources [16,17].…”
Section: Virtual Water Inflows From the Nation And The Metropolitan Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, network and multi-network approaches provide a mathematical framework for the integrated characterization and modeling of the system (e.g., producers, consumers, transfers, etc.) underlying the WF [35,73]. Additional information and examples of the application of network analysis to WF studies can be found elsewhere [71,[73][74][75].…”
Section: Water Footprint Assessment (Wfa)mentioning
confidence: 99%
“…Further investigation of grey water analysis in urban regions is needed and a complete urban WF analysis will need to consider all the flows identified in Figure 1. Recently, a generalization of EEIO and EFA methods, termed Embedded Resource Accounting (ERA), was proposed and developed [35,73,141]. ERA makes explicit the assumptions implied by the different footprint standards and methods, and in doing so it not only adds transparency to footprint analysis but it also facilitates the integration of different datasets (e.g., IO tables, commodity flows, etc.).…”
Section: A General Approach For Urban Water Footprint Analysismentioning
confidence: 99%